Strategic resilience in human performance in the context of science and education - perspective - Ziehr, Sabrina; Merkt, Philipp Hans (Frontiers in Psychiatry, 2024)
Introduction Special situations that jeopardize the internal and external security for communities are increasing in their frequency and complexity. This creates complicated challenges for individuals, governments and humanity. National and international strategies are being developed that focus on the resilience and coping of all first responders during these extreme stress states. Aim The aim of the article is to present the framework of strategic resilience, its multidimensional measurement and the possibilities for training robust resilience to increase operational effectiveness in special operational situations. Methodological approach Research in the area of special operation situations often focuses on the human performance cluster. The Unit of Applied Research 18_RECESS (18_ Research and Education Center for Extraordinary Tactical Situations and Strategically Resilience) at the Department of Disaster Prevention and Crisis Management at Fresenius University of Applied Sciences in Idstein fits into this field. It pursues the adaptation of existing resilience models to special operation situations in line with the definition of strategic resilience. In addition, the focus is on the possibility of training strategic resilience to increase operational effectiveness. There are currently several research projects being conducted in the civilian and civilian-military sectors, as well as with ground and special operations forces. Major findings Strategic Resilience with its 3 axes Psychological, Physiological and Cognitive Resilience covers the core domains of various existing models of resilience. This provides an adequate concept to describe different factors leading to personnel perseverance in special operation situations. There exists the possibility to train several domains of strategic resilience via problem-oriented intervention (POH).